A Rare Case of an Ectopic Liver Presenting as Right Atrial Mass - Adhirath Doshi; Dhaval Shah; Shradha Gupta; Deepika Panday; Arie Farji-Cisneros; Eddison Ramsaran; Robert Bojar (Case Reports in Cardiology)
Ectopic liver tissue is commonly observed in the abdominal cavity in adjacent organs. Extension of hepatic tissue into the intrathoracic cavity is rarely reported. We present the case of a 46-year-old woman with a 2.1×1.8 cm mass confirmed by transesophageal echocardiogram to be at the right atrial and inferior vena cava junction that was initially thought to be a myxoma which prompted surgical excision but subsequently identified as ectopic liver by histology.